Course design and teaching practice in STEAM education at distance via an interactive e-learning platform: A case study. Issue 2 (2nd December 2019) - Chen, Wu; Tang, Xin; Mou, Ting
Abstract : Purpose: The purpose of this paper is to provide some references for teachers who use KidsProgram or other graphic programming tools platform for STEAM (science, technology, engineering, arts and mathematics) education at distance by game-based teaching. From the design of the STEAM class, teachers can know how to stimulate students' interest in programming and cultivating their ability to innovate and solve practical problems more clearly with KidsProgram. Design/methodology/approach: This paper will explain the teaching design from ten aspects and implement it in real class to see the result. The ten aspects are situations creation, knowledge popularization, raising problems, analyzing problems, concepts introduction, interface design, logic design, self-evaluation and mutual evaluation, teacher comments and extension and innovation. With the KidsProgram platform, this paper takes "The Missile Convey, " a sub-course of "Discovery Universe" as an example. Through the situation created by the teacher, students brainstorm the dangers that the earth may encounter in the universe and then learn relevant scientific knowledge. Next, students raise and analyze problems according to the situation under the guidance of the teacher. Through the interaction with teachers, students review the programming concepts and the usage of corresponding coding blocks needed for the project, like "random number." They need to carry out interface design and logic design for the project, and complete the project. After that, the students use the self-evaluation form and the mutual evaluation form to modify and then show and share the projects to the in front of the class. After self-evaluation and peer evaluation, the teacher will make a final summary evaluation and make some suggestions for improvement. From the students' programming productions and the interviews with them, the teaching result can be known. Findings: With elaborate teaching design and appropriate teaching strategies, students can flexibly use multi-disciplinary knowledge of science, technology, engineering, art and mathematics to solve problems in the process of creation, which is conducive to the cultivation and improvement of students' comprehensive quality on KidsProgram classroom, under the guidance of STEAM education. In other words, in this class, students need to use engineering thinking to plan the whole project based on the understanding of scientific principles, design interfaces with artistic ideas, use mathematical knowledge for logical operations, and gradually solve technical problems with the above knowledge or methods in a comprehensive way. Originality/value: The KidsProgram is a leading graphical programming tool platform in China in recent years. It deeply reconstructs the concept of Scratch designed by MIT. Graphic programming, a method of programming by dragging and dropping blocks containing natural languages, is different from traditional code programming. In this paper, the visualized cases in the class will be demonstrated in the "interface design" and "logic design." This paper designs a course in STEAM education at distance via KidsProgram, hoping to provide some reference for other research on teaching of graphical programming tools.